Sustainable Water Resource Management Using IOT Solution for Agriculture - Kadar H.H.; Sameon S.S.; Rafee P.A. (Institute of Electrical and Electronics Engineers Inc., 2023)
Agricultural products; Agricultural robots; Control systems; Food supply; Internet of things; Interoperability; Resource allocation; Water conservation; Water levels; Water management; Agriculture industries; Emergent technologies; Internet of Things (IOT); Leakage monitoring systems; Sustainable water resources; Water management systems; Water resources management; Waterresource management; Information management